2004
DOI: 10.1292/jvms.66.893
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Canine Babesia gibsoni Infection and Subclinical Infection among Tosa dogs in Aomori Prefecture, Japan

Abstract: ABSTRACT. To identify the incidence of Babesia gibsoni (B. gibsoni) in Aomori Prefecture, northeastern Japan, dogs with acute B. gibsoni infection were investigated at the Animal Teaching Hospital, Kitasato University, between April 2002 and March 2003. Eighteen dogs with acute B. gibsoni infection were recognized; they were all male dogs of the fighting dog breed Tosa. Their platelet counts were below normal and their packed cell volumes (PCVs) were at various levels. We collected blood samples from 141 Tosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…However, Haemaphysalis longicornis, a predominant tick species in dogs, is known to transmit B. gibsoni [11]. It is widely distributed throughout Japan, including eastern Japan, the area of this study [17]. Thus, it is also possible that B. gibsoni is transmitted through blood from infected dogs to ticks and may be established among ticks in the eastern part of Japan.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Haemaphysalis longicornis, a predominant tick species in dogs, is known to transmit B. gibsoni [11]. It is widely distributed throughout Japan, including eastern Japan, the area of this study [17]. Thus, it is also possible that B. gibsoni is transmitted through blood from infected dogs to ticks and may be established among ticks in the eastern part of Japan.…”
Section: Discussionmentioning
confidence: 92%
“…In Japan, it is distributed mainly in the western part [3,4,7,8] and only a few epidemiological and clinical studies have been reported on canine B. gibsoni infection in eastern Japan. All of the confirmed cases of B. gibsoni infection in the eastern part of Japan were found among Tosa dogs, a fighting breed raised only in Aomori Prefecture [3,10,17]. Transmission of B. gibsoni in this area was thought not to occur via ticks [3], although the vector tick species, Haemaphysalis longicornis, is distributed throughout Japan [19].…”
mentioning
confidence: 99%
“…B. gibsoni infected dogs are generally seen in the west of Japan and dogs affected by B. canis are mainly observed on Okinawa island. However, the incidence of canine babesiosis, especially B. gibsoni infection, has been recently reported to be increasing, and the areas affected are expanding towards the northeastern part of Japan [15,17,27]. Clinical symptoms of canine babesiosis include anorexia, depression and exercise intolerance as a result of hemolytic anemia.…”
mentioning
confidence: 99%
“…B. gibsoni infected dogs either clinical patient or experimental are required for this method. Our laboratory established a continuous culture of B. gibsoni isolated from Tosa dogs (Matsuu et al, 2004a). There is no precise report emphasizing the efficacy of doxycycline sensitivity alone in vitro against B. gibsoni by RT-PCR.…”
Section: Introductionmentioning
confidence: 99%